AcuFocus Corneal Inlay to Correct Presbyopia Using Femto-LASIK. One Year Results of a Prospective Cohort Study - Jalali, S.; Aus der Au, W.; Shaarawy, T. (Klinische Monatsblätter für Augenheilkunde, 2016)
Purpose: To evaluate the safety and efficacy of the AcuFocus small aperture corneal inlay (KAMRA) for the correction of presbyopia using femto-LASIK. Patients and Methods: This is a prospective, non-randomised cohort study including 50 presbyopic patients with hyperopia, emmetropia or mild myopia. The intracorneal inlay was implanted in the non-dominant eye using a VisuMax femtosecond laser (Zeiss 500 kHz) to create a superior-hinged flap. The inlay was centred over the visual axis. Minimum postoperative follow-up was performed for a period of 12 months. Results: Fifty intracorneal inlays were implanted. At one year follow-up, the median uncorrected near visual acuity significantly improved from Jaeger (J)8 to J2 (p < 0.001). 94 % of patients could read J3 or better. The median uncorrected distance visual acuity also improved from 20/32 to 20/22 (p < 0.001). 92 % of patients could see 20/32 or better. One implant had to be recentred at four weeks follow-up. One implant was removed six months after implantation due to insufficient uncorrected near and distance visual acuity as well as slight corneal haze, which resolved four weeks later under topical treatment with fluorometholone eye drops, without any loss of best corrected distance visual acuity. No other complications occurred during the postoperative follow-up period. Conclusion: AutoFocus Corneal Inlay (ACI), also known as KAMRA, can provide a safe, effective and, most importantly, reversible treatment for presbyopia in hyperopic, myopic and emmetropic patients.
Keywords: intracorneal inlay; KAMRA; presbyopia; Femto-Lasik